New Synthetic Method and Antioxidant Activity of Betulin Diformate and Allobetulin Formate; Chemistry of Natural Compounds; Vol. 55, iss. 6 - Arrous S. Salah; Boudebouz I. Imene; Parunov I.; Plotnikov E. V. Evgeny Vladimirovich; Voronova O. A. Olesya Aleksandrovna (2019, 2019)
Title screen